Descending thoracic aortic dissection after covered stent for adult aortic coarctation: Technical or physiopathologic? - Caiyun Liu; Xuening Dai; Guangqi Zhou; Yi Zhang; Xinmei Liu (Heliyon, 2023)
Covered stent graft implantation is currently the most commonly used modality for the management of adult aortic coarctation. Although the risk of descending thoracic aortic dissection after covered stent graft implantation is low, sometimes it may cause serious medical consequences or even death. We report one adult aortic coarctation patient with early postoperative descending thoracic aortic dissection after covered stent graft implantation. The patient underwent second operation of thoracic endovascular aortic reconstruction and was discharged 6 days after the operation. This case is not rare, but we hope that the complete diagnosis and treatment process of this case and discussion pertaining to surgical treatment method and its complications could serve as a reference for clinicians in dealing with such situations.